The relationship between leadership style and employee engagement at Pejabat Setiausaha Kerajaan Terengganu / Iffa Maisarah Nazri - Nazri, Iffa Maisarah (Faculty of Business and Management, 2018)
The purpose of this research was to investigate the relationship between leadership style and employee engagement. This correlational study used a simple random sampling and the sample size was determined by using Krejcie and Morgan (1970). Survey questionnaires were distributed to 123 employees at Pejabat Setiausaha Kerajaan Terengganu as respondents. The Statistical Package for the Social Sciences (SPSS) version 23 is used to analyze the data collected. The descriptive statistics such as mean and standard deviations are used to analyze the data, answer the research questions and describe the research objectives. Majority of the respondents were female, aged 26 to 35 years old. Many of them are from Human Resource Management Department. The findings showed that there was a moderate relationship between Transactional leadership and employee engagement. Then, the findings showed that there was a moderate relationship between Transformational leadership and employee engagement. The result also showed that the level of engagement among employees at Pejabat Setiausaha Kerajaan Terengganu is at moderate level.